Chondropenia followed by epidemic of osteoarthritis: from joint aging to the clinical manifestations - A. V. Naumov; N. O. Hovasova; O. N. Tkacheva (Лечащий Врач, 2021)
Osteoarthritis (OA) is the most wide-spread and socially significant disease of musculoskeletal system. Systemic inflammation and formation of proinflammatory cytokines underlie OA, which, in its turn, conditions keeping pain syndrome and cartilage degradation. Currently, theory of chondropenia, due to age-related reduction of glycosaminoglycans, is actively developed. Modern complex OA therapy should include glycosaminoglycans.